Pengaruh Kualitas Air Pendederan Ikan Lele Sangkuriang (Clarias gariepinus) dI BBI Teun - Pelu, Anselmus Mau; Liubana, Debora Victoria (Jurnal Akuakultur Sungai dan Danau, 2025)
Sangkuriang catfish (Clarias gariepinus) is one of the cultivated commodities that has a selling value. Sangkuriang catfish is the result of genetic engineering as an effort to improve the quality of dumbo catfish. Sangkuriang catfish nursery is carried out in three nursery stages, namely nursery I for 14-21 days, nursery II for 21-28 days, and nursery III for 28-35 days. The success of catfish cultivation requires the availability of good quality seeds in sufficient quantities on an ongoing basis. Good water quality for catfish growth, temperature 26-30, pH 6.5-8.5, DO ≥ 5.